La promoción de los procesos metacognitivos en la enseñanza de la ciencia a partir del conocimiento local: un caso desde el ámbito rural de Colombia (Ensayos) - Ramírez Ruz, Carmen María (2024)
Considering local knowledge as a key element for the teaching of natural sciences in rural environments is an opportunity to foster public understanding of science from this scenario. To this, cognitive and metacognitive strategies are added that allow rethinking the roles of those who interact through teaching-learning. The arguments presented allow generating a debate on the importance given to the rural school as an epicenter of knowledge derived from the local level and that does not go beyond beliefs lacking in meaning for those who cohabit the countryside, thus promoting scientific literacy based on their intellectual possibilities. In view of the above, this essay presents reflections that invite us to take another look at the formative act, urging us to visualize an educational process that overcomes the prominence given to practices that defend the homogenization of knowledge. In this sense, the edges that derive from the school-community interrelation are contemplated, emphasizing the ways in which people act in the rural context; under this assumption, importance is given to the imaginaries that provide information about the sociocultural and natural richness of the Colombian rurality.